The Safety, Immunogenicity, and Immunopersistence of Hepatitis A Vaccine in HBs-Ag-Positive Participants: A Retrospective Study - Wang, Xiaodan; Luo, Jia; Ma, Fubao; Kang, Guodong; Ding, Zhengrong; Pan, Yue; Zhao, Yujiao; Chen, Junying; Feng, Kai; Yan, Lingmei; Zhang, Juan; Li, Linhao; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: To compare the safety, immunogenicity, and immune persistence of hepatitis A (HA) vaccines between HBs-Ag-positive and -negative participants. Method: 9000 participants were enrolled in the phase IV study of live attenuated HA (HA-L) or inactivated HA (HA-I) vaccines. The HBs-Ag-positive subjects were detected and became an independent observation group. Adverse reactions (ARs), geometric mean concentrations (GMCs) and seroconversion rates (SRs) of the vaccines were analyzed at five time points untill three years after vaccination. Results: 120 HBs-Ag-positive subjects were screened out, only 1 participant had grade 1 experienced ARs after HA-L injection. Except the time point of two years, the SRs of HBs-Ag-positive group were 100% for both vaccines. The GMCs were not statistically different between HBs-Ag-positive and -negative groups after the HA-L vaccination. The logarithmically transformed GMCs for HBs-Ag-positive and -negative groups were 3.21 mIU/mL (95% CI, 2.03-4.39 mIU/mL) and 2.95 mIU/mL (95% CI, 2.88-3.02 mIU/mL) 28 days after the HA-L vaccination, respectively. Conclusions: Both HA-L and HA-I vaccines were safe for HBs-Ag-positive participants and may provide an excellent long-term protection against HAV in this study. The results indicated that people positive or negative for HBs-Ag can receive both HA-L and HA-I vaccines (ClinicalTrials.gov number, NCT02601040).